The Effect of employee competence on performance of microfinance institutions in Nakuru town, Kenya - Gachuru, George (Editon Consortium Journal of Business and Management Studies, 2020)
The study was carried out to establish the effect of employee competence on the performance of microfinance institutions in Nakuru CBD. The study is significant to the MFI in that it will benefit management and staff of MFI and the government understudy by gaining insights into how their institution can effectively deal with the problems that they encounter in managing their clients and to ensure they grow their business. A survey design was used for the study. The target population comprised of 35 respondents. These were Branch managers, Chief Credit officer/s and the IT support of the MFI in Nakuru CBD. The study used census method as the small size of the target population could easily be managed. A questionnaire containing closed-ended questions was used as the data collection instrument for the study. Descriptive statistics, including percentages and frequencies, was adopted for data analysis Results were presented in the form of charts, tables and graphs. The study established that the level of employee competence affects the implementation of online banking to a large extent. Based on this finding the researcher recommended that microfinance institutions should have some training programs to help improve on the customers level of skills because some consumers do not have the required skills and facilities needed to do online banking and this will allow for the smooth running of operations.